In vitro response of Perna viridis hermocytes to Pyrodinium bahamense var. compressum vegetative cells - Capati, Ma. Carol Salamat; Azanza, Ma. Patricia V. (2001., 2001)
In this study, the in vitro response of green mussel (Perna viridis) hemocytes to vegetative Pyrodinium bahamese var. compressum cells was examined. A method of extracting P. viridis hemolymph was first established for use in all experiments of the study. Morphological types and viability (within 0-24h) of P. viridis hemocytes were determined prior to observations on the in vitro interaction between P. viridis hemocytes and Pyrodium. Extraction of P. viridis hemolymph from the posterior adductor muscle through dorsal entry was found to be the most satifactory among 3 extraction methods studied. Except for bacteria, all artifacts in the other 2 procedures were eliminated by this extraction method. The hemolymph sample value yielded by this method ranged within 3.7-7.4 ml per mussel. Four morphological types of hemocytes were identified in P. viridis hemoplymph: granulocytes, hyalinocytes, brown cells, and partially granular cells. The predominant type was the granulocyte, comprosing 94.4% of the hemocytes. Some evidence indicated that some of the non-granular cell types may either be artifactual or exist as morphological variants of the granulocytes. The% viability of P. viridis granulocytes in vitro declined with time, as determined by nigrosin dye exclusion method. The percentage of viable P. viridis granulocytes was highest (90.4%) at ) 0 h, and > 80% up to 5 h. Hemocytes of p. viridis in vitro responded to vegetative Pyrodinium cells by encapsulating the dinoflagellate (60% of replicates). The degree of encapsulation varied among replicates: Complete encapsulation is characterized by envelopment of the entire dinoflagellate by hemocytes, while partial encapsulation was either by adherence of several hemocytes to the Pyrodinium or the formation of hemocyte aggregates on some surfaces of the dinoflagellates. It was hypothesized that the interaction varied among replicates due to a number of factors related to the experimental methods and the in vivo conditions of the mussel/dinoflagellate sample. The hemocytic encapsulation of Pyrodinium may have implied that P. viridis hemocytes recognize the dinoflagellate as foreign, and that some constituents from Pyrodinium may have been immune elicitors in P. viridis hemolymph. In this study, the positive interaction between P. viridis hemocytes and vegetative Pyrodinium cells in vitro was reported for the last time. It is still unclear whether hemocytes in vivo are involved in the processing of P. bahamense var. compressum cells in P. viridis. The occurence of such hemocytic mechanisms may be determined by endoscopy of histological examination of Pyrodinium-exposed mussels.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Mussels -- Microbiology